N-Acetylcysteine for Cardiac Protection During Coronary Artery Reperfusion: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Khan, Sher Ali; Campbell, Ashley M.; Lu, Yingying; An, Lingling; Alpert, Joseph S.; Chen, Qin M. (Frontiers in Cardiovascular Medicine, 2021)
Coronary artery reperfusion is essential for the management of symptoms in patients with myocardial ischemia. However, the benefit of reperfusion often comes at an expense of paradoxical injury, which contributes to adverse events, and sometimes heart failure. Reperfusion is known to increase the production of reactive oxygen species (ROS). We address whether or not N-acetylcysteine (NAC) reduces ROS and alleviates reperfusion injury by improving clinical outcomes. Literature searches for randomized controlled trials (RCTs) were carried out in 5 biomedical databases for testing the effects of NAC in patients undergoing coronary artery reperfusion by percutaneous coronary intervention, thrombolysis or coronary artery bypass graft. Of 787 publications reviewed, 28 RCTs were identified, with a summary of 2174 patients. Meta-analysis using the random effects model indicated that NAC administration during or prior to reperfusion procedures resulted in a trend towards a reduction in the level of serum cardiac troponin (cTn) [95% CI, SMD -0.80 (-1.75; 0.15), p=0.088, n=262 for control, 277 for NAC group], and in the incidence of postoperative atrial fibrillation [95% CI, RR 0.57 (0.30; 1.06), p=0.071, n=484 for control, 490 for NAC group]. The left ventricular ejection fraction or the measures of length of stay in intensive care unit or in hospital also displayed a positive trend that was not statistically significant. Among the 9 trials that measured ROS, 7 showed a correlation between reduction of lipid peroxidation and improved clinical outcomes. These lines of evidence support the potential benefit of NAC as an adjuvant therapy for cardiac protection against reperfusion injury.